ANALISIS MOTIVASI KERJA GURU DI SMA NEGERI 9 SEMARANG - Moh. Makhbub Aly; Eko Yuliyanto (Universitas Muhammadiyah Semarang, 2018)
Intrinsic and extrinsic motivation is a factor that can affect the performance of the teacher. Motivation work encouragement against the teachers so that the resulting teacher performance can be more optimally. The purpose of this research is to find out how big the motivation of working teachers in SMA Negeri 9 Semarang. This research uses a quantitative approach and Descriptive Survey method. The population in this study are all teachers at SMA Negeri 9 Semarang. The sample in this study is 20 teachers were taken based on table Krecjie. The techniques used in sampling that is using Random Sampling System Technique. The variable in this study is the motivation of working as free variables (X) using data collection Techniques, observation, question form, interview and documentation. Data processing in this research using SPSS software. from research that has been done can conclude that intrinsic motivation as a teacher in the SMA Negeri 9 Semarang earns an average score of 81.78 can be categorized veryhigh. While for Extrinsic Motivation gain score with average of 77.88% and can be categorized high. Keywords: Motivation of working, teachers, qualitative approach, SMA Negeri 9 Semarang